Implementation Of Creating Shared Value (CSV) In Corporate Social Responsibility (CSR) Programs To Enhance Business Value And Employee Performance (Case Study Of PT Len Industri (Persero), Bandung, West Java) - Anristy Sadira Pinem; Defrizal Defrizal (UNIVED Press, 2025)
This study investigates the implementation of Creating Shared Value (CSV) in Corporate Social Responsibility (CSR) programs at PT Len Industri (Persero), focusing on the SolarPump and SolarTree initiatives. By aligning societal and business objectives, these programs have demonstrated tangible impacts, including increased corporate revenue, enhanced employee performance, and improved public reputation. The SolarPump initiative addresses clean water scarcity in rural areas, while SolarTree provides urban communities with access to renewable energy solutions. The findings reveal that CSV not only enhances business value through market expansion and revenue growth but also improves employee motivation, skill development, and loyalty. This study concludes that CSV is a strategic approach capable of fostering sustainable development and corporate competitiveness, providing valuable insights for businesses seeking to integrate social impact with their core objectives